IMPROVING SPEAKING SKILLS: STRATEGIES AND TECHNIQUES - Eshonqulov Ravshan Toxirovich; Jurayev Azizbek Ikromjon ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Speaking is a key element of effective communication, impacting personal, academic, and professional interactions. This article explores strategies to enhance speaking skills, focusing on clarity, pronunciation, confidence, audience engagement, and expanding vocabulary. Drawing from experts such as Dale Carnegie, Russ Harris, and Carmine Gallo, the article provides techniques for improving speech in both native and second languages. Techniques such as pronunciation practice, storytelling, and impromptu speaking exercises are discussed to build confidence and fluency. The article also emphasizes the importance of public speaking skills, highlighting the role of preparation and effective delivery. Through regular practice and application, individuals can become more effective and engaging speakers.